The H3K4 methyltransferase Setd1b is essential for hematopoietic stem and progenitor cell homeostasis in mice - Kerstin Schmidt; Qinyu Zhang; Alpaslan Tasdogan; Andreas Petzold; Andreas Dahl; Borros M Arneth; Robert Slany; Hans Jörg Fehling; Andrea Kranz; Adrian Francis Stewart; Konstantinos Anastassiadis (eLife, 2018)
Hematopoietic stem cells require MLL1, which is one of six Set1/Trithorax-type histone 3 lysine 4 (H3K4) methyltransferases in mammals and clinically the most important leukemia gene. Here, we add to emerging evidence that all six H3K4 methyltransferases play essential roles in the hematopoietic system by showing that conditional mutagenesis of Setd1b in adult mice provoked aberrant homeostasis of hematopoietic stem and progenitor cells (HSPCs). Using both ubiquitous and hematopoietic-specific deletion strategies, the loss of Setd1b resulted in peripheral thrombo- and lymphocytopenia, multilineage dysplasia, myeloid-biased extramedullary hematopoiesis in the spleen, and lethality. By transplantation experiments and expression profiling, we determined that Setd1b is autonomously required in the hematopoietic lineages where it regulates key lineage specification components, including Cebpa, Gata1, and Klf1. Altogether, these data imply that the Set1/Trithorax-type epigenetic machinery sustains different aspects of hematopoiesis and constitutes a second framework additional to the transcription factor hierarchy of hematopoietic homeostasis.